Conductive Elastomers: A Metal‐Like Conductive Elastomer with a Hierarchical Wrinkled Structure (Adv. Mater. 7/2020). Issue 7 (18th February 2020) - Lee, Seokmin; Song, Yongkwon; Ko, Yongmin; Ko, Younji; Ko, Jongkuk; Kwon, Cheong Hoon; Huh, June; Kim, Sang‐Woo; Yeom, Bongjun; Cho, Jinhan
Abstract : In article number 1906460, Bongjun Yeom, Jinhan Cho, and co‐workers introduce a metal‐like conductive elastomer with hierarchical wrinkled structure that is induced by in situ cooperation of solvent swelling and densely packed nanoparticle assembly. The formed elastomer electrode shows exceptional electrical performance and mechanical stability, and can be directly applied to the preparation of fully elastomeric electronics.